Boundary element analysis of fibre-bridging in fibre-metal laminates - Gan, Rui Yun (2017)
To analyse fibre-bridging in cracked fibre-metal laminates, a numerical study using the Boundary Element Method was done. In this study, the material used is Glass-Reinforced Aluminium Laminate (GLARE). The study was conducted using the BEM, with varying parameters, to obtain the fibre-bridging stress and normalised crack-tip stress intensity factors (SIF). The parameters varied were crack configurations, crack size ratio, extent of fibre-bridging, power law index and delamination shape. The computational results were analysed and the impact of the variation of each parameter on the fibre-bridging stress and crack-tip stress intensity factor (SIF) was observed. Generally, it was noticed that both fibre-bridging stresses and normalised crack-tip SIF increase with the increase in crack size and power law index, and the decrease in the extent of fibre-bridging. The values of fibre-bridging stresses are generally lower in circular delamination, in comparison to elliptical delamination, while the values of normalised crack-tip SIF are generally lower in elliptical delamination instead. This study allowed a better understanding of the fibre-bridging mechanism in fibre-metal laminates, particularly GLARE, qualitatively without going through the more sophisticated Finite Element Method.